Reconstructing the Third Wave of Democracy: Comparative African Democratic Politics - Edozie, Rita Kiki (Hamilton Books, 2008)
Since the 1990s, trends in African politics require the realization that the public policy practice and the theoretical analysis of 'democracy and democratization' are becoming increasingly important tenets for understanding the contemporary political science of the region. Reconstructing the Third Wave of Democracy explains these new political processes and ideas. Author Rita Kiki Edozie identifies factors that Africans have encountered since the foundation of the modern African state and presents a critical analysis of African politics through the lenses of post-colonial discourse by uniquely employing the ideas of democratic theory to guide an analysis of the Continent's democratic development and performance. Edozie presents an intra-regional comparative analysis of democratic politics in Africa in ways that few books on the same subject do for the continent. Her methodology for examining democracy in Africa reveals the dynamism of several country cases and several more regime experiences with democracy encountered from the post-World War II period to the current post-Cold War period.